Effect of PM concentration on anemia blood indicators reduced by air purifiers. (May 2023) - Kwag, Youngrin; Oh, Jongmin; Yang, Wonho; Kim, Yangho; Ha, Eun-Hee; Ye, Shinhee
Abstract: Housewives perform daily household chores, which directly expose them to indoor particulate matter (PM). Indoor PM exposure is a potential factor that increases systemic inflammation and affects hematopoietic action. This study investigated the decrease in indoor PM concentration by air purifiers on indicators of anemia, such as hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). We analyzed the data of 40 housewives who were subjected to an air purifier intervention in Seoul and Ulsan, Republic of Korea. Indoor exposure levels of PM2.5 and PM10 were analyzed with sensor adjusted and gravimetric measurement. We also investigated the same anemia indicators before and after the installation of an air purifier for three months (short-term: one month, long-term: three months). Statistical analysis was performed by a multiple linear model and a linear mixed model. The indoor PM exposure levels and air purifier use were related to anemia indicators (hemoglobin and MCHC). The increase in indoor PM2.5 level was associated with a decrease in MCHC (β: 0.034, P = 0.031) and hemoglobin (β: 0.013, P = 0.04). The decrease in indoor PM2.5 concentration by air purifier was associated with an increase in MCHC (β: 0.204, P = 0.087) and hemoglobin (β: 0.190, P = 0.039). In particular, after air purifier intervention, the amounts of MCHC and hemoglobin significantly increased. Our results suggest that indoor air purifier use could decrease indoor PM level and the risk of anemia to housewives. Because the effect on anemia is subacute, it was confirmed three months after air purifier operation. In conclusion, anemia indicators can be improved by PM reduction management. Highlights: Housewives are involved in household chores, which expose them to indoor PM. Indoor PM is a factor that increases inflammation and affects hematopoietic action. Results is that indoor air purifier use decreases PM and impacts anemia indicators. In conclusion, anemia indicators can be improved by fine dust reduction management.